Comparative Analysis of ITGΒ6 Gene Expression in Oral Cancer - Abdullah Ahmad; Asma Ahmad (AlQalam Journal of Medical and Applied Sciences, 2024)
The goal of this study was to determine the quality and quantity of ITGβ6 gene expression in oral squamous cell carcinoma (OSCC). Two Cell lines (H357) and (Vβ6) were used to analyses β6protein and gene expression by using BAC assay, SDS-PAGE gel, and western blotting, agarose gel as well as real- time PCR techniques. The western blotting and real-time PCR studies demonstrated high level of protein expressions in the transected Vβ6 cells line which shown as clear thick band. On the other hand, a protein expression of H357 cells line was less and gives weak band. Therefore, Squamous cell lines from the oral mucosa that express β6 are linked to increased invasion and progression. This highlights the significance of understanding cancer progression mechanisms and the impact of varying expression levels in different tumors.